EXAMINING THE PSYCHOLOGY OF WORKING THEORY AMONG NIGERIAN COLLEGE STUDENTS - (:unkn) unknown (My University, 2025)
STUDY 1: EXAMINING PREDICTORS AND OUTCOMES OF FUTURE DECENT WORK PERCEPTION AMONG NIGERIAN EMERGING ADULTSHigh levels of poverty and unemployment are pervasive barriers to Nigerian emerging adults entering the job market (Olorunfemi, 2021). The current study employed the Psychology of Working Theory ( Duffy et al., 2016) to explore career engagement, academic satisfaction, and life satisfaction predictors in a nation experiencing the intersections of high poverty and high unemployment rate. We tested a model predicting these outcomes from economic constraints and marginalization mediated by work volition, career adaptability, and perceptions of future decent work. We administered online surveys to 310 undergraduates in Nigeria. Career adaptability and work volition predicted the perception of future access to decent work. Also, those who reported higher chances of securing decent work after graduation reported greater academic and life satisfaction and career engagement. While economic constraints predicted career adaptability in this model, marginalization did not predict career adaptability. In contrast with previous studies, economic constraints, and marginalization were not predictive of work volition or future decent work perception. We also found a positive relationship between economic challenges and career adaptability against the propositions of the Psychology of Working Theory (PWT). The implications of our findings were discussed. STUDY 2: QUALITATIVE EXAMINATION OF PSYCHOLOGY OF WORKING THEORY AMONG NIGERIAN EMERGING ADULTS.This study utilized qualitative document analysis (QDA) to explore the perceptions of 443 Nigerian college students regarding future access to decent work in sub-Saharan Africa, amidst high unemployment rates. Guided by the Psychology of Working Theory (PWT) and Nigerian cultural dynamics, we delved into their definitions of decent work, barriers hindering access, available choices within these constraints, and the impact of these perceptions on academic outcomes and well-being. Notably, participants viewed decent work as more than just a source of income, indicating its reflection of personal values and societal norms, emphasizing the complex interplay of individual agency, systemic obstacles, and socio-economic environments in shaping career outlooks and academic outcomes. In addition, our research expands the PWT framework by introducing new dimensions of decent work perception such as social protection and market economy, underlining the necessity for cross-cultural investigations to refine existing theories and measures. These results inform future research inquiries and provide actionable insights for policymakers and professionals working with Nigerian college students.   STUDY 3: PREDICTING WORK VOLITION AMONG NIGERIAN EMERGING ADULTS: A PSYCHOLOGY OF WORKING PERSPECTIVE This study employed hierarchical regression analysis to evaluate the predictors of work volition within Nigeria's collective cultural context, drawing from the Psychology of Working (PWT) perspective. In a sample of 375 participants, we found that familial guidance and a sense of belonging in the university community significantly influence the perception of control over one’s choice of career amidst barriers. Surprisingly, economic constraints and marginalization showed minimal impact on work volition, contrasting with PWT's central tenets. Our findings emphasize the importance of disseminating accurate career information and fostering inclusive campus environments to support career development among Nigerian youths. This research contributes to the ongoing discourse on cultural responsiveness in vocational psychology and offers practical insights for career counseling programs tailored to Nigerian contexts.
Keywords: Counseling psychology; career adaptability; future decent work perception; multicultural vocational research; Psychology of Working Theory; work volition; youth unemployment in Nigeria